A Comparative Study of Ethnic Discrimination in Employment Law in Iraq and Iran - Sedeeq Mohammad, Dashti; Farkish, Hana; Sharifi, Arkan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Discrimination in employment rights refers to unequal pay and benefits, access to job opportunities, and career advancement among individuals based on factors such as gender, race, ethnicity, religion, age, and social status. In Iraq, the country’s constitution guarantees equal rights for all Iraqi citizens, regardless of ethnicity, race, religion, and other factors. Additionally, Iraqi labor and employment laws prohibit ethnic discrimination and require employers to act without regard to ethnicity when hiring and promoting employees. Similarly, in Iran, the country’s constitution guarantees equal rights for all Iranian citizens. Iranian labor and employment laws also prohibit ethnic discrimination and require employers to act without regard to ethnicity when hiring and promoting employees. Despite the clarity of the laws in both countries, ethnic bias and favoritism have unfortunately replaced meritocracy in many organizations and institutions. This type of discrimination can have detrimental effects on individuals and society, as ethnic discrimination in employment rights violates the principle of social justice. This research paper, with a descriptive-analytical approach and relying on library documents, addresses the issue of employment rights and compares the two countries of Iraq and Iran. The comparative results of the present study show that both countries are committed to guaranteeing equal rights and benefits for their citizens. However, in Iran, discriminatory policies exist that lead to ethnic discrimination in certain industries and specific jobs and in Iraq, ethnic discrimination is illegal, and there is no difference between Iraqi citizens in employment.